Three cobalt-based coordination polymers with tripodal carboxylate and imidazole-containing ligands: syntheses, structures, properties and DFT studies. Issue 66 (26th November 2019) - Tang, Long; Wang, Huan-Huan; Fu, Yu-Hao; Wang, Yi-Tong; Wang, JiJiang; Hou, XiangYang
Abstract : The tripodal carboxylate ligand can be employed in Co(ii ) salt/imidazole-containing ligand systems to generate 1D chain, 2D layer, and 2D to 3D network, and the fluorescence properties of 1–3 and magnetic behavior of 1 and 2 have been investigated. Abstract : Three cobalt-based coordination polymers [Co(Htatb)(1, 3-bimyb)] (1 ), [Co(Htatb)(bimbp)]·DMF (2 ), and [Co(Htatb)(1, 4-bimyb)]·H2 O (3 ) [H3 tatb = 4, 4′, 4′′- s -triazine-2, 4, 6-tribenzoic acid, 1, 3-bimyb = 1, 3-bis(imidazole-1-ylmethyl)benzene, bimbp = 4, 4′-bis(imidazolyl)biphenyl, 1, 4-bimyb = 1, 4-bis (imidazole-1-ylmethyl)benzene] were synthesized by hydrothermal reactions and characterized by single-crystal X-ray diffraction, thermogravimetric analyses, IR spectroscopy, UV-vis spectroscopy and elemental analysis. Compound 1 shows a double-strand chain structure, due to the intermolecular O–H⋯O hydrogen bonds and aromatic π–π stacking interactions, the adjacent chains are connected to produce a 3D supramolecular structure. Compound 2 shows a 2D structure with a 1D channel. Compound 3 displays a 2D layer structure, furthermore these layers are joined by O–H⋯O hydrogen bonding to generate a four-fold interpenetrating 3D architecture. The fluorescence properties of 1–3 and the magnetic behavior of 1 and 2 have also been investigated. Based on their crystal structures, compounds 1 and 2 were investigated using hybrid DFT methods at the B3LYP/6-31G (d) level. The DFT-BS approach was applied to study the magnetic coupling behavior. The results reveal that the calculated exchange coupling constants J were in good agreement with the experimental data.